Meso research on the fiber orientation distribution of aramid fiber‐reinforced rubber composite. (1st October 2020) - Gao, Jianhong; Jiao, Fuxing; Zhang, Hongjian; Lin, Xiaoshan; Huang, Lihong; Guo, Jinquan; Yang, Xiaoxiang
Abstract : Aramid fiber‐reinforced rubber composites (AFRCs) have attracted considerable attention due to their excellent mechanical properties. These mechanical properties provide the composites with a certain degree of anisotropy due to the fiber orientation distribution (FOD) in the AFRCs, thereby allowing them to flexibly meet requirements based on different scenarios. However, the quantitative determination of FOD in AFRCs continues to be a challenge. In this study, the triple ion‐beam cutting technique was proposed to obtain high‐quality polished cross‐sections of the AFRCs. An image processing technique was used to separate the rubber matrix and the fiber in the optical micrograph. The fiber orientation information was extracted based on the shape of the fiber section. The FODs of the AFRCs were described using the probability function. Finally, the mechanical property was evaluated using a 2D finite element analysis. The agreement between the experimental and numerical results validated the effectiveness of the proposed method.